Episodic Memories in Anxiety Disorders: Clinical Implications - Zlomuzica, Armin; Dere, Dorothea; Machulska, Alla; Adolph, Dirk; Dere, Ekrem; Margraf, Jürgen (Frontiers in Behavioral Neuroscience, 2014)
The aim of this review is to summarize research on the emerging role of episodic memories in the context of anxiety disorders (AD). The available literature on explicit-, autobiographical- and episodic memory function in AD including neuroimaging studies is critically discussed. We describe the methodological diversity of episodic memory research in AD and discuss the need for novel tests to measure episodic memory in a clinical setting. We argue that alterations in episodic memory functions might contribute to the etiology of AD. We further explain why future research on the interplay between episodic memory function and emotional disorders as well as its neuroanatomical foundations offers the promise to increase the effectiveness of modern psychological treatments. We conclude that one major task is to develop methods and training programs that might help patients suffering from AD to better understand, interpret and possibly actively use their episodic memories in a way that would support therapeutic interventions and counteract the occurrence of symptoms.